Sistem Informasi Manajemen Kepegawaian Modul Time Management (Studi Kasus: Politeknik Negeri Subang) - Sisnawati; Azhariyah, Sari; Vernanda, Dwi (Jurnal Sistem Informasi Galuh, 2025)
The purpose of this study is to resolve issues with Subang State Polytechnic's personnel data processing. The method for determining remaining leave and requesting employee leave is currently semi-manual due to the outdated technology. Numerous significant aspects of the system are included, such as the ability to use QR code signatures, store information, and apply for leaves of absence. Employees will be able to correctly and conveniently record their attendance with the attendance tool. With the help of the leave application function, employees won't have to visit the personnel department in person to complete the leave application procedure. This study develops a system using the Fountain Method, which includes requirements analysis, system design, implementation, and testing phases. To assure the quality and dependability of the system, testing is done utilizing UAT techniques and black box testing. A 98% success rate was attained by the system that underwent black box testing, and the results were favorable, demonstrating that all functions work as intended. Additionally, 83% of the questions had been correctly answered, according to data from User Acceptance Testing (UAT). Thus, it can be said that the system makes it easier to handle leave, attendance, and information notifications.